Integrating Islamic work ethics in work from home arrangement - Siti Suraya Abd Razak; Siti Zaharah Jamaluddin; Faridah Hanim Jaffri (Penerbit Universiti Kebangsaan Malaysia, 2022)
The COVID-19 pandemic has resulted in changes in the way working is perceived. The concept of work from home which was previously only associated with specific types of work has had to be implemented for many sectors in Malaysia. This concept is novel in Malaysia, thus creating a lot of uncertainties in both law and practice, including the issue of work ethics. This mode of working may be the new norm in the future, which makes it important to examine the work ethics for work from home. The objectives of this study are firstly, to analyse the concept of Islamic work ethics, and secondly, to integrate Islamic work ethics in a work from home arrangement. It is believed that the application of Islamic work ethics by both the employers and the employees may avoid conflicts at work due to different expectations. In this context, the research is based on secondary sources and analyses of existing literature, and on reading of Islamic texts (the Quran and Hadith). Islamic work ethics consist of universal values where they underline the responsibilities of employer to live up to promises, consider an employee’s situation, negotiate with an employee to improve their contract, and equal treatment of employees. Apart from that, employees are also responsible for keeping their promises, being honest, working in a team and performing their jobs in good faith. This research found that Islamic work ethics can hinder conflicts between employer and employee. They are suitable for integration in working from home arrangements as the new normal in Malaysia and directly encourage the implementation of organisational justice.